ANTI-MITOCHONDRIAL ANTIBODY NEGATIVE PRIMARY BILIARY CIRRHOSIS: A CASE REPORT - Badshah, Aliena; Humayun, Mohammad (Journal of Postgraduate Medical Institute, 2016)
Primary Biliary Cirrhosis (PBC) is an idiopathic, cholestatic destruction of intra- hepatic microscopic bile ducts. Up to 80% of the patients presenting with PBC are females. Patients usually present with fatigue, pruritis and jaundice. Suspicion of PBC arises when cholestasis and cirrhosis are present in middle-aged women. Anti-mitochondrial antibodies (AMA) are present in 95% of the patients. AMA is considered the serological hallmark of PBC, but may be absent in a proportion of these patients. We hereby present a case of AMA-negative PBC.